The role of ecosystems for start-ups: a comparative study between Korea and Findland - Deschryvere, Matthias; Kim, Younghwan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
The strategic importance of innovation ecosystems has received increased attention from both the academic and policy perspectives. However, there is only limited empirical evidence on the importance of these ecosys- tems from the perspective of younger firms. This study focuses on the role of ecosystems for young innovative companies (YICs) and is based on a unique set of phone survey data from Finland and South Korea. The re- sults are threefold: (i) Finnish YICs participate more actively in ecosystems than Korean YICs; (ii) on aver- age, Korean YICs report to have experienced lower ecosystem impact compared to Finnish YICs; (iii) in both countries, key organizations of the ecosystems are represented on the board of directors in about one-third of the sample firms.